Job Satisfaction: Linking Discipline, Environment, Communication to Employee Performance: Kepuasan Kerja: Hubungan Disiplin, Lingkungan Kerja, Komunikasi dengan Kinerja Karyawan - Rani Arianti Safitri; Mudji Astutik (Academia Open, 2022)
This quantitative study investigated the influence of work discipline, work environment, and communication on employee performance, with job satisfaction as the mediating variable. The research was conducted at a company, and the sample comprised 161 employees. Path analysis was employed as the analytical tool, utilizing a questionnaire program with a Likert scale to measure variables. The findings revealed significant effects of work discipline, work environment, and communication on job satisfaction. Additionally, work discipline, work environment, and communication were found to significantly impact employee performance. Job satisfaction was found to have a significant effect on employee performance as well. However, no indirect effects were observed between work discipline, work environment, and communication on employee performance through job satisfaction as an intervening variable. These findings contribute to the understanding of the factors that influence employee performance and highlight the importance of fostering work discipline, creating a conducive work environment, and promoting effective communication in organizations. Highlights: Job satisfaction enhances employee performance. Effective work discipline promotes higher job satisfaction. A positive work environment and communication positively impact job satisfaction. Keywords: Employee Performance, Work Discipline, Work Environment, Communication, Job Satisfaction